(3eNJda GdTjYI aj CMcGe GdTQjYIs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi deG hbaJ Ydi cJH CUMGHfG GdeJbOejf s
(3BNQgG (B:s
(3MJi jNQL ef ecI eSGaQkG ajbUO GdSaQ YfO NQhLg ef ecI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B303s
Keywords: (3abg GdePGgH GdCNQis